Long-term outcomes of catheterizable continent urinary channels: What do you use, where you put it, and does it matter?. Issue 4 (August 2015) - Szymanski, Konrad M.; Whittam, Benjamin; Misseri, Rosalia; Flack, Chandra K.; Hubert, Katherine C.; Kaefer, Martin; Rink, Richard C.; Cain, Mark P.
Summary: Introduction: Appendicovesicostomy (APV) and Monti ileovesicostomy (Monti) are commonly used catheterizable channels with similar outcomes on short-term follow-up. Their relative long-term results have not been previously published. Objective: Our goal was to assess long-term durability of APV and Monti channels in a large patient cohort. Study design: In this retrospective cohort study, we retrospectively reviewed consecutive patients ≤21 years old undergoing APV and Monti surgery at our institution (1990–2013). We collected data on demographics, channel type, location, continence and stomal and subfascial revisions. Kaplan–Meier survival and Cox proportional hazards analysis were used. Results: Of 510 patients meeting inclusion criteria, 214 patients had an APV and 296 had a Monti (50.5% spiral Monti). Median age at surgery was 7.4 years for APV (median follow-up: 5.7 years) and 8.7 years for Monti (follow-up: 7.7 years). Stomal stenosis, overall stomal revisions and channel continence were similar for APV and Monti ( p  ≥ 0.26). Fourteen APVs (6.5%) had subfascial revisions compared to 49 Montis (16.6%, p  = 0.001). On survival analysis, subfascial revision risk at 10 years for APV was 8.6%, Monti channels excluding spiral umbilical Monti: 15.5% and spiral umbilical Monti: 32.3% ( p  < 0.0001, Figure). On multivariate regression, Monti was 2.09 times more likely than APV to undergo revision ( p  = 0.03). The spiral Monti to the umbilicus, in particular, was 4.23 times more likely than APV to undergo revision ( p  < 0.001). Concomitant surgery, gender, age and surgery date were not significant predictors of subfascial revision ( p  ≥ 0.17). Stomal location was significant only for spiral Montis. Discussion: Our study has several limitations. Although controlling for surgery date was a limited way of adjusting for changing surgical techniques, residual confounding by surgical technique is unlikely, as channel implantation technique was typically unrelated to channel type. We did not include complications managed conservatively or endoscopically. In addition, while we did not capture patients who were lost to follow-up, we attempted to control for this through survival analysis. Conclusions: We demonstrate, durable long-term results with the APV and Monti techniques. The risk of channel complications continues over the channel's lifetime, with no difference in stomal complications between channels. At 10 years after initial surgery, Monti channels were twice as likely to undergo a subfascial revision (1 in 6) than APV (1 in 12). The risk is even higher in for the spiral umbilical Monti (1 in 3).